The Effect of Acceptance and Commitment Group Therapy on the Psychological Well-being and Happiness of Children of Divorce - Soroush Zolghadri; Ahmad Borjali; Farideh Hoseinsabet (پژوهش‌های کاربردی روانشناختی, 2024)
The aim of this study was to ascertain the effect of Acceptance and Commitment Group Therapy on the psychological well-being and happiness of Divorce Children. The design of this study was practical and quasi-experimental, with pretest-posttest follow-up and a control group. The study’s statistical population comprised all children of divorce aged 13 to 17 who had access to the social networks Instagram, WhatsApp, and Telegram in Iran in 2022. Convenience sampling was employed to select thirty individuals, who were then randomly assigned to control and experimental groups. Acceptance and Commitment Therapy was administered to the experimental group for a total of eight sessions. The Ryff Psychological Well-Being Scale (RSPWB) and the Oxford Happiness Inventory (OHI) were employed in this investigation. Repeated Measures ANOVA was used in SPSS software version 26 for data analysis. The results of repeated-measures ANOVA (P˂0.01) showed an increase in psychological well-being and happiness scores of the experimental group compared to the control group. Additionally, the results of the follow-up indicated that the treatment’s effects persisted over time. Given the significant efficacy of Acceptance and Commitment Group Therapy, it is advised that this treatment be considered as a means of enhancing the psychological well-being and increasing happiness of divorced children.